The cognitive reserve theory in the setting of pediatric-onset multiple sclerosis. (November 2016) - Pastò, Luisa; Portaccio, Emilio; Goretti, Benedetta; Ghezzi, Angelo; Lori, Silvia; Hakiki, Bahia; Giannini, Marta; Righini, Isabella; Razzolini, Lorenzo; Niccolai, Claudia; Moiola, Lucia; Falautano, Monica; et al.
Background: The study of cognitive reserve (CR) in relationship with cognitive impairment (CI) in pediatric-onset multiple sclerosis (POMS) may provide cues to identifying subjects at higher risk of impairment and scope for therapeutic strategies. Objectives: To assess the potential impact of CR on cognition in a cohort of POMS patients. Methods: In all, 48 POMS patients were followed up for 4.7 ± 0.4 years. CI was defined as the failure of ⩾3 tests on an extensive neuropsychological battery. Change of neuropsychological performance was assessed through the Reliable Change Index (RCI) method. At baseline, CR was estimated by measuring the intelligence quotient (IQ). The relationships were assessed through multivariable regression analyses. Results: At baseline, CI was detected in 14/48 (29.2%) patients. Two out of 57 healthy control (HC; 3.5%) met the same criteria of CI ( p  < 0.001). A deteriorating cognitive performance using the RCI method was observed in 18/48 patients (37.6%). Among the 34 cases who were cognitively preserved at baseline, a higher reserve predicted stable/improving performance (odds ratio (OR) = 1.11; 95% confidence interval (CI): 1.03–1.20; p  = 0.006). Conclusion: Our results suggest that higher CR in POMS patients may protect from CI, particularly in subjects with initial cognitive preservation, providing relevant implications for counseling and rehabilitation strategies.